Towards an Appraisal of Biodiversity in Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2023)
In this paper, the concept of biodiversity has been presented on a historical perspective keeping the visions on Bangladesh via mentioning the primary supporting climatological and physiographic factors of the ecosystems along with their species composition. The total number of microbes, plant, and animal species has been estimated in the range of 10,606-14,913. The varieties of ecosystems present in Bangladesh belong to the broad categories, namely forest, agro-terrestrial, freshwater aquatic, as well as estuarine and marine. Forests cover nearly 17.5% of the total land of Bangladesh having specific categories like tropical wet evergreen and semi-evergreen, tropical moist deciduous, mangrove, freshwater swamp, and homestead forests. Dominant species belonging to those ecosystems were mentioned. The dimension of crop diversity in Bangladesh is very large, but the most common staple food comes from Oryza sativa, Triticum aestivum and Zea mays. The sources of biodiversity for the supply of vegetable and protein have been highlighted. Unique biodiversity in cases of freshwater phytoplankton and aquatic plants has been provided. Results from a case study on butterfly as their qualitative and quantitative biological population dynamics in 34 forest ecosystems of Bangladesh were presented and discussed. The establishment of an open ‘Butterfly Park’ in a National Park reveals that with due course of time the plant-butterfly-wildlife vertebrate species interaction increases with a concomitant increase in the biodiversity. Dominant plant and animal species together with their status as endemic, endangered, threatened, etc. in variously defined ecosystems of Bangladesh were highlighted. Besides, the ways of biodiversity conservation currently in practice in Bangladesh has been mentioned along with the future plans and programs to be implemented. Bangladesh holds a rich history in the starting of biodiversity teaching via developing curricular activities in different teaching institutions throughout the country. The origin and background of this activity was also highlighted. This review will help researchers to address biodiversity related questions on a scientific perspective.J. Biodivers. Conserv. Bioresour. Manag. 2023, 9(1): 79-100